Default cascades: When does risk diversification increase stability? - Battiston, Stefano; Gatti, Domenico Delli; Gallegati, Mauro; Greenwald, Bruce; Stiglitz, Joseph E. (Journal of Financial Stability, 2012)
We explore the dynamics of default cascades in a network of credit interlink-ages in which each agent is at the same time a borrower and a lender. When some counterparties of an agent default, the loss she experiences amounts to her total exposure to those counterparties. A possible conjecture in this context is that individual risk diversification across more numerous counterparties should make also systemic defaults less likely. We show that this view is not always true. In particular, the diversification of credit risk across many borrowers has ambiguous effects on systemic risk in the presence of mechanisms of loss amplifications such as in the presence of potential runs among the short-term lenders of the agents in the network.